Potential and Strength of Social Capital of Dewi Shinta's WASIAT (Healthy Alert Citizens) Group Assisted by CSR PT Kilang Pertamina Internasional (KPI) RU V Balikpapan - Muntiyati; Nugrahani , Lifania Riski; Firdaus, M. Zayyan Abiyusa (Prospect Publishing, 2024)
PT Kilang Pertamina Internsional (KPI) RU V Balikpapan has implemented a CSR program based on empowerment through the Program Warga Siaga Sehat (Wasiat) Dewi Shinta in Penajam Paser Utara Regency. This study aims to determine the form and potential of social capital of the Wasiat Group in Girimukti Village, Penajam District, Penajam Paser Utara Regency, East Kalimantan. This study uses a descriptive qualitative approach with data collection techniques in the form of literature studies, observations, in-depth interviews, and documentation of research objects. The research concept used is the social capital concept from Putnam (2000), which groups social capital into bonding social capital, bridging social capital, and social linking. The research results in Wasiat show the existence of bonding social capital, namely cooperation and mutual cooperation in the implementation of the Wasiat program. Bridging social capital, the Wasiat Group also became a lottery group. Linking Social Capital, manifested in the form of cooperation between the Wasiat Program and several parties, namely companies, Girimukti Village Government, Bumdes Girimukti, Health Office, Petung Puskesmas and Kenari Group. Social capital plays an important role in the existence of the Wasiat Group.